Citius and longius (faster and longer) with no α-actinin-3 in skeletal muscles?. Issue 9 (8th February 2007) - Lucia, Alejandro; Oliván, Jesús; Gómez-Gallego, Félix; Santiago, Catalina; Montil, Marta; Foster, Carl
Abstract : The muscle protein α-actinin-3 (ACTN3) is normally thought to be expressed in type II muscle fibres and to be necessary for high-power, high-velocity muscle contractions, such as those typically seen in speed/power athletes. The authors report the case of a Spanish elite long jumper (two times Olympian, personal best of 8.26 m) whose genotype for the ACTN3 gene is 577XX (ACTN3 deficient). These data suggest that there might be notable exceptions to the concept that ACTN3 is the "gene for speed".